Análisis temporal de reducción de emisión de gases en áreas de caña de azúcar cosechadas mecánicamente utilizando imágenes satelitales - Arraes, Christiano Luna; Camacho-Tamayo, Jesús; Pissarra, Teresa Tarlé; Bueno, Célia P.; Campos, Sergio (My University, 2010)
The primary objective of this study was to estimate the amount of gas not emitted into the air in areas cultivated with sugarcane (Saccharum officinarum) that were mechanically harvested. Satellite images CBERS-2/CCD, from 08-13-2004, 08-14-2005, 08-15-2006 and 08-16-2007, of northwestern São Paulo State were processed using the Geographic Information System (GIS)-IDRISI 15.0. Areas of interest (the mechanically-harvested sugarcane fields) were identified and quantified based on the spectral response of the bands studied. Based on these data, the amount of gas that was not emitted was evaluated, according to the estimate equation proposed by the Intergovernmental Panel on Climate Change (IPCC). The results of 396.65 km2 (5.91% for 2004); 447.56 km2 (6.67% for 2005); 511.54 km2 (7.62% in 2006); and 474.60 km2 (7.07% for 2007), calculated from a total area of 6,710.89 km2 with sugarcane, showed a significant increase of mechanical harvesting in the study area and a reduction of gas emissions of more than 300,000 t yr-1.
Temporal analysis of the reduction in gas emission in areas of mechanically-harvested sugarcane using satellite imagery
Keywords: Geographic information system; Orbital image; Remote sensing; Saccharum officinarum